2020
DOI: 10.1210/clinem/dgaa909
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal-Neonatal Steroids With Early Pregnancy Endocrine Disrupting Chemicals and Pregnancy Outcomes

Abstract: Context Steroids play an important role in fetal development and parturition. Gestational exposures to endocrine disrupting chemicals (EDCs) affect steroidal milieu and pregnancy outcomes, raising the possibility of steroids serving as biomarkers. Most studies have not addressed the impact of EDC mixtures, which are reflective of real life scenarios. Objective Assess the association of maternal and neonatal steroids with preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 106 publications
1
6
0
Order By: Relevance
“…Our group has previously demonstrated that steroids increase during pregnancy to promote fetal and placenta development and ultimately parturition. 60 In our previous work, 21 multiple lipid spe-cies�PCs, PEs, SMs, and triacylglycerols (TG)�containing long and very long chain polyunsaturated fatty acids were higher in CB than M3, provisioning essential fatty acids for the developing fetal brain. 51 The untargeted metabolomics platform supported these results, demonstrating significant increases of several long chain polyunsaturated PCs and PEs in CB.…”
Section: ■ Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our group has previously demonstrated that steroids increase during pregnancy to promote fetal and placenta development and ultimately parturition. 60 In our previous work, 21 multiple lipid spe-cies�PCs, PEs, SMs, and triacylglycerols (TG)�containing long and very long chain polyunsaturated fatty acids were higher in CB than M3, provisioning essential fatty acids for the developing fetal brain. 51 The untargeted metabolomics platform supported these results, demonstrating significant increases of several long chain polyunsaturated PCs and PEs in CB.…”
Section: ■ Discussionmentioning
confidence: 93%
“…Using MS/MS spectral search, several of the features that most significantly increased from M1 to M3 were identified as steroid hormones. Our group has previously demonstrated that steroids increase during pregnancy to promote fetal and placenta development and ultimately parturition . In our previous work, multiple lipid speciesPCs, PEs, SMs, and triacylglycerols (TG)containing long and very long chain polyunsaturated fatty acids were higher in CB than M3, provisioning essential fatty acids for the developing fetal brain .…”
Section: Discussionmentioning
confidence: 96%
“…( 27 ) The 3‐hydroxy‐delta‐5‐steroids were quantitated after liquid–liquid extraction with methyl‐tert‐butyl ether and derivatization as picolinic acid esters, using a Kinetex 50 x 2.1 mm, 2.6‐μm particle size biphenyl resolving column and an Agilent 6490 tandem mass spectrometer as described. ( 28,29 )…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, steroid therapy should be initiated only in those patients who are likely to give birth within two weeks of the start of the therapy. The use of prenatal steroids may be associated with maternal side effects and result in generalized bacterial infection, tuberculosis, and viral infections (shingles, Herpes); uncontrolled metabolic diseases, including diabetes and unresponsive hypertension; or active gastric ulcer and duodenum [ 60 , 61 ]. However, the risk of generalized fetal and maternal infection occurrence should not decide about initiating the prophylactic intervention, as the advantages of earlier pulmonary development were proven and are much higher than the side effects of steroids administration [ 30 , 58 ].…”
Section: Clinical Issuesmentioning
confidence: 99%